'No politics in the agenda-setting meeting': plenary agenda setting in the Netherlands. Issue 4 (7th June 2019) - Otjes, Simon
Abstract: The process of agenda setting is fundamental to politics, yet there is surprisingly little research about this process in parliamentary systems. The reason for this lacuna is that agenda setting tends to occur behind closed doors. The Dutch Tweede Kamer is an exception to this rule: decisions about the parliamentary agenda are made in public. This study examines agenda setting in the Dutch parliament from an issue-competition perspective. It looks at a sample of more than 400 agenda-setting meetings of the Dutch parliament between 1998 and 2017. It finds that opposition parties which stand far from the government make proposals on issues that they 'own'; these proposals are supported by other opposition parties, parties that stand close to them and focus on the same issue. Coalition parties and parties that stand far away sabotage these proposals.